Serum semicarbazide-sensitive amine oxidase (SSAO) activity is an independent marker of carotid atherosclerosis - Karádi, István; Mészáros, Zsuzsa; Csányi, Attila; Szombathy, Tamás; Hosszúfalusi, Nóra; Romics, László; Magyar, Kálmán (Clinica chimica acta, 2002)
Background: Clinical and experimental studies suggest that increased activity of semicarbazide-sensitive amine oxidase (SSAO) and the production of cytotoxic metabolites (e.g., formaldehyde and hydrogen peroxide) may play an important role in the pathogenesis of atherosclerosis. The present study was designed to assess the relationship between the increased activity of the enzyme and the severity of atherosclerosis in diabetic and control subjects. Methods: The study included 29 patients with type 2 diabetes mellitus and 25 control subjects. Human serum SSAO activity was determined by using 14C-benzylamine as substrate. Mean common carotid intima–media thickness (IMT), Crouse score and Bogousslawsky score was evaluated by color-coded, high-resolution duplex carotid sonography. Results: Serum SSAO activity was significantly increased in patients with type 2 diabetes compared to controls. Carotid plaque score (Crouse score), total cholesterol level and age-corrected intima–media thickness showed positive correlation with enzyme activity in control subjects. In patients with diabetes, serum SSAO activity correlated with the severity of carotid stenosis (Bogousslawsky score) as well as the carotid plaque score. Conclusions: Determination of serum SSAO activity might be a candidate biochemical marker of early atherosclerosis and diabetic macrovascular complications.